2021
DOI: 10.3390/ijms22179578
|View full text |Cite
|
Sign up to set email alerts
|

Canady Helios Cold Plasma Induces Breast Cancer Cell Death by Oxidation of Histone mRNA

Abstract: Breast cancer is the most common cancer among women worldwide. Its molecular receptor marker status and mutational subtypes complicate clinical therapies. Cold atmospheric plasma is a promising adjuvant therapy to selectively combat many cancers, including breast cancer, but not normal tissue; however, the underlying mechanisms remain unexplored. Here, four breast cancer cell lines with different marker status were treated with Canady Helios Cold Plasma™ (CHCP) at various dosages and their differential progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 85 publications
2
17
0
Order By: Relevance
“…Initially identified in our previous studies on carcinoma cell lines [38,43], inhibition of Ki67 expression and initiation of apoptosis by CHCP was replicated in this study on liposarcoma cells. We also observed a spike in the number of liposarcoma cells in the S/G2/M phase followed by initiation of cell death, consistent with our recent study on breast cancer cell lines [38]. This previous study demonstrated that CHCP permanently disrupts the cell cycle through specific 8-oxoG modification of histone mRNA during the early S-phase.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Initially identified in our previous studies on carcinoma cell lines [38,43], inhibition of Ki67 expression and initiation of apoptosis by CHCP was replicated in this study on liposarcoma cells. We also observed a spike in the number of liposarcoma cells in the S/G2/M phase followed by initiation of cell death, consistent with our recent study on breast cancer cell lines [38]. This previous study demonstrated that CHCP permanently disrupts the cell cycle through specific 8-oxoG modification of histone mRNA during the early S-phase.…”
Section: Discussionmentioning
confidence: 52%
“…This previous study demonstrated that CHCP permanently disrupts the cell cycle through specific 8-oxoG modification of histone mRNA during the early S-phase. This compromises the stability of histone mRNA, leading to chromatin destabilization and apoptotic cell death [38]. Although this was demonstrated in breast cancer cells, it is possible that CHCP also induces oxidation of histone mRNA in liposarcoma cells, which will require confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a drastic reduction in G1 phase cells and an increase in S/G2 phase cells compared to control groups after CHCP treatment at 80p 5 min is because of the histone mRNA degradation and a pause in cell division which in turn accumulates more cells at late S phase 37 . This phenomenon is more pronounced in cells treated with siRNA-BCL2A1 in combination with the CHCP treatment suggesting that silencing BCL2A1 expression increases cell death.…”
Section: Discussionmentioning
confidence: 95%
“…Complete inhibition of cell proliferation by downregulation of MYC expression and G1 cell cycle arrest was observed after CPI203 treatment in neuroendocrine tumors 38 . Recently we showed that degradation of histone mRNA during the early S phase of the cell cycle, rather than DNA damage, is the primary cause of cancer cell death induced by CHCP 37 . How the cell cycle arrest induced by CPI203, and histone mRNA degradation induced by CAP treatment would increase the potency of cell death in combination should be determined.…”
Section: Discussionmentioning
confidence: 99%